Can a renewal movement be renewed?: questions for the future of ecumenism - Kinnamon, Michael (William B. Eerdmans Publishing Company, 2014)
Does ecumenism have a future? -- What would it mean to take the "next step" in ecumenical and interfaith relations -- Is the ecumenical movement a movement for peace? -- What can the churches say together about the church? -- What can the churches say together about the environment? -- Can the tension between unity and justice be overcome? -- Has the ecumenical movement become too "political"? -- What is the way forward for Catholic-Protestant relations? -- How can the Orthodox help others understand them better? -- How are interfaith relationships as challenging as they are necessary? -- How can we deal with the tough issues in Jewish-Christian relations? -- Are councils of churches a thing of the past? -- What does it take to be an ecumenical leader? -- What will it take to revitalize the ecumenical movement? -- Why care about Christian unity when there are so many other things to worry about?